The design of an instrumented charpy impact tester using the deconvolution method - Chua, Alvin Y. (Animo Repository, 1994)
This study aims to modify the conventional Charpy Impact Tester by making it instrumented or computerized, so as to expand its data gathering and handling capabilities. First, auxiliary devices like the centering jig, the centering tongs, and the calibration jig for the Charpy head will be designed and fabricated. Second, electronic data gathering equipments will be installed together with the corresponding software to gather the strain response coming from the strain group. Third, a software will be designed to display the different characteristic graphs. Finally, a laboratory operating procedure will be designed so as to standardize the operation of the Instrumented Charpy Impact tester.